KAJIAN YURIDIS TENTANG IMPLEMENTASI JAMINAN KESEHATAN BAGI WARGA MISKIN DAN/ATAU TIDAK MAMPU DI KOTA SEMARANG - Amelia Rizky Budiyanto; Muzayanah Muzayanah (Jurnal Ilmiah Dinamika Hukum, 2020)
Based on Article 28 H paragraph (1) of the 1945 Constitution. Local governments have the responsibility to fulfill the right to health services for their citizens so that citizens have the right to health services. Thus the Semarang City Government ratified Semarang Mayor Regulation Number 43 of 2017 concerning the Implementation of Health Insurance. The poor and neglected children are cared for by the state, this is stated in article 34 paragraph (1) of the 1945 Constitution. Through the UHC program, the Semarang City Government provides health services to its citizens. The purpose of this study was to determine the implementation of health insurance, especially for the poor and underprivileged in order to improve the public health status. This type of research uses the juridical-normative method, namely by describing the prevailing laws and regulations associated with legal theories and practice of implementing positive law relating to problems. Juridical-normative research is in accordance with the research conducted by the author, because in this study the writer tries to describe the existing facts or existing facts and describe a problem that exists in the implementation of Semarang Mayor Regulation No. 43 of 2017 concerning the Implementation of Health Insurance. With the existence of PBI and UHC, it has helped the community in terms of costs, but it should be added that the Semarang City Regulation Number 43 of 2017 has not regulated in more detail regarding outpatient care so that it still causes a cost burden felt by the community. And also the government still needs to disseminate information about the UHC program, as evidenced in the 3rd (third) year the program is running there are still people who do not know about the program. It is a shame that the benefits of this program cannot be felt by the community as a whole. Keywords: Implementation, Health Insurance, The Poor